Pembuatan keputusan multi-kriteria untuk kenaikan pangkat kakitangan akademik di institusi pengajian tinggi awam - Khairul Anuar Mohd Ali; Wan Salmuni Wan Mustaffa (Penerbit ukm, 2007)

(untitled)
The issue of academic staff promotion in Higher Educational Institution (HEI) is very challenging and always gives rise to controversy. This research discusses the academic staff promotion in Public Institution of Higher Learning by using Analytic Hierarchy Process (AHP) technique. AHP technique is used to determine and obtain the priorities of importance (weights) to the component and criteria for academic staff promotion. The criteria developed will cover 4 major components which consist of Research and Publications, Teaching, Services and Personality. The data was analyzed based on three principles in AHP technique: the principle of constructing hierarchies, the principle of relative comparison and the principle of synthesizing priorities. The study found that the most important components in deciding academic staff promotion are Research and Publications with a weightage of (0.3919). The range of consistency value is between (0.0000) and (0.0114)